Oral immunization of carps with chitosan–alginate microcapsule containing probiotic expressing spring viremia of carp virus (SVCV) G protein provides effective protection against SVCV infection. Issue 105 (October 2020) - Jia, Shuo; Zhou, Kun; Pan, Ronghui; Wei, Jing; Liu, Zhongmei; Xu, Yigang
Abstract: Spring viremia of carp (SVC) is highly contagious and lethal disease in cyprinid fish, in particular common carps ( Cyprinus carpio ), causing numerous economic losses to the aquaculture industry. SVC is presently endemic disease in Europe, America, and several countries in Asia and its causative agent is spring viremia of carp virus (SVCV). In this study, a chitosan-alginate microcapsule probiotic vaccine expressing G protein of SVCV was prepared, and the immunogenicity in carps of orally administrated with the microcapsule probiotic vaccine was evaluated. Our results showed that the microcapsule probiotic vaccine can induce potent antigen-specific immune responses in carps via oral vaccination, and provide effective anti-SVCV protection for carps. Significantly, the microcapsule probiotic vaccine is suitable for mass fish immunization, suggesting a promising vaccine strategy for fish. Highlights: Chitosan-alginate microcapsule probiotic vaccine expressing SVCV G protein was developed. The microcapsule probiotic vaccine has good immunogenicity in carps via oral vaccination. The microcapsule probiotic vaccine can provide effective anti-SVCV protection for carps. The microcapsule oral probiotic vaccine is convenient for mass fish immunization.